Advanced Hip Implants: Combining a novel metastable beta-Ti alloy and lattice structures to reduce stress shielding (Transactions on Additive Manufacturing Meets Medicine, 2025)
Total Hip Replacement is a widely performed and highly effective procedure for restoring hip function in patients with degenerative joint conditions [1]. However, stress shielding remains a major challenge, as the stiffness mismatch between the bone and the implant may cause bone resorption and implant instability, potentially leading to the need for revision surgeries. This study explores a combined strategy to address this issue by integrating Ti21S, a promising novel beta-metastable titanium alloy for biomedical applications with a lower elastic modulus than conventional Ti6Al4V, and lattice structures, to enhance stiffness compatibility and osteointegration [2]. Two prosthetic designs were investigated: the first incorporates TPMS (Triply Periodic Minimal Surface) and auxetic lattice structures, while the second relies solely on TPMS, both with varying relative densities to optimize load distribution. TPMS structures are particularly advantageous for orthopedic devices due to their high surface area, interconnected porosity, zero-mean curvature and mechanical properties that closely mimic trabecular bone, promoting osteointegration and reducing stiffness mismatch [3]. Furthermore, the integration of auxetic structures in a specific implant region subjected to compressive-loading is designed to leverage the negative Poisson’s ratio, ensuring continuous bone adhesion and stimulation [4]. Mechanical performance was assessed through fatigue and quasi-static compression tests, while Digital Image Correlation (DIC) was used to analyze surface deformation. Microstructural analysis identified potential manufacturing defects, and Finite Element Method (FEM) simulations, simplified via homogenization, were conducted to validate experimental findings. Results showed that the proposed designs achieved promising stiffness values comparable to bone, but fatigue resistance remained suboptimal due to printing defects, the absence of heat treatments, and the application of testing standards designed for bulk implants rather than lattice-based structures. This study highlights the potential of combining low-modulus metastable beta-titanium alloys with mechanical metamaterials to develop next-generation orthopedic implants that reduce stress shielding, minimize bone resorption, and improve long-term stability, ultimately decreasing the need for revision surgeries.[1] S.A. Naghavi, M. Tamaddon, P. Garcia-Souto, M. Moazen, S. Taylor, J. Hua, C. Liu, A novel hybrid design and modelling of a customised graded Ti-6Al-4V porous hip implant to reduce stress-shielding: An experimental and numerical analysis, Front. Bioeng. Biotechnol. 11 (2023) 1–20. https://doi.org/10.3389/fbioe.2023.1092361.[2] L. Emanuelli, M. Babaei, R. De Biasi, A. Plessis, A. Trivisonno, F. Agostinacchio, A. Motta, M. Benedetti, M. Pellizzari, Optimising ? -Ti21S Alloy Lattice Structures for Enhanced Femoral Implants?: A Study on Mechanical and Biological Performance, Materials (Basel). 18 (2025) 170. https://doi.org/10.3390/ma18010170.[3] F.S.L. Bobbert, K. Lietaert, A.A. Eftekhari, B. Pouran, S.M. Ahmadi, H. Weinans, A.A. Zadpoor, Additively manufactured metallic porous biomaterials based on minimal surfaces: A unique combination of topological, mechanical, and mass transport properties, Acta Biomater. 53 (2017) 572–584. https://doi.org/10.1016/j.actbio.2017.02.024.[4] H.M.A. Kolken, A.F. Garcia, A. Du Plessis, C. Rans, M.J. Mirzaali, A.A. Zadpoor, Fatigue performance of auxetic meta-biomaterials, Acta Biomater. 126 (2021) 511–523. https://doi.org/10.1016/j.actbio.2021.03.015.
Keywords: 3D-Printed Implants; Beta titanium alloy; stress shielding; Laser Powder Bed Fusion; lattice structures